Pengelolaan Sistem Drainase Berbasis Partisipasi Masyarakat di Kecamatan Tanggulangin, Kabupaten Sidoarjo - Alfian Huda Aunur Hasyir; Wahyu Aunur Rahman Hakim (Jurnal Studi Multidisiplin Qomaruna, 2026)
Rapid population growth and land-use changes in urban areas often reduce the capacity of drainage systems, leading to waterlogging in residential neighborhoods. This condition is also evident in Tanggulangin District, Sidoarjo Regency, where several residential areas experience drainage dysfunction due to inadequate channel capacity and weak environmental management. This study aims to analyze the condition of residential drainage systems and formulate community-based management strategies. A descriptive qualitative approach was employed using the Participatory Rural Appraisal (PRA) method, involving local residents, village officials, and technical agencies. Data were collected through field observations, semi-structured interviews, Focus Group Discussions (FGDs), and documentation. The findings indicate that most drainage channels in the three study villages, Kedungbanteng, Banjarpanji, and Kalidawir, have experienced narrowing and siltation caused by sediment accumulation and domestic waste. Approximately 60% of the tertiary drainage network is not connected to the main secondary channels, resulting in frequent waterlogging in residential areas. Furthermore, community participation in drainage maintenance remains sporadic and lacks formal institutional organization. The study highlights that community-based drainage management, through participatory drainage mapping, the establishment of community-level drainage monitoring teams, and the implementation of simple infiltration technologies such as infiltration wells and biopores, can strengthen surface water management capacity in a more adaptive and sustainable manner.